Acute Intoxication With Alcohol Reduces Trauma-Induced Proinflammatory Response and Barrier Breakdown in the Lung via the Wnt/β-Catenin Signaling Pathway - Noack, Laurens; Bundkirchen, Katrin; Xu, Baolin; Gylstorff, Severin; Zhou, Yuzhuo; Köhler, Kernt; Jantaree, Phatcharida; Neunaber, Claudia; Nowak, Aleksander J.; Relja, Borna (Frontiers in Immunology, 2022)
Background Trauma is the third leading cause of mortality worldwide. Upon admission, up to 50% of traumatized patients are acutely intoxicated with alcohol, which might lead to aberrant immune responses. An excessive and uncontrolled inflammatory response to injury is associated with damage to trauma-distant organs. We hypothesize that, along with inflammation-induced apoptosis, the activation of the Wnt/β-catenin signaling pathway would cause breakdown of the lung barrier and the development of lung injury after trauma. It remains unclear whether ethanol intoxication (EI) prior to trauma and hemorrhagic shock will attenuate inflammation and organ injury. Methods In this study, 14 male C57BL/6J mice were randomly assigned to two groups and exposed either to EtOH or to NaCl as a control by an oral gavage before receiving a femur fracture (Fx) and hemorrhagic shock, followed by resuscitation (THFx). Fourteen sham animals received either EtOH or NaCl and underwent surgical procedures without THFx induction. After 24 h, oil red O staining of fatty vacuoles in the liver was performed. Histological lung injury score (LIS) was assessed to analyze the trauma-induced RLI. Gene expression of Cxcl1, Il-1β, Muc5ac, Tnf, and Tnfrsf10b as well as CXCL1, IL-1β, and TNF protein levels in the lung tissue and bronchoalveolar lavage fluid were determined by RT-qPCR, ELISA, and immunohistological analyses. Infiltrating polymorphonuclear leukocytes (PMNLs) were examined via immunostaining. Apoptosis was detected by activated caspase-3 expression in the lung tissue. To confirm active Wnt signaling after trauma, gene expression of Wnt3a and its inhibitor sclerostin (Sost) was determined. Protein expression of A20 and RIPK4 as possible modulators of the Wnt signaling pathway was analyzed via immunofluorescence. Results Significant fatty changes in the liver confirmed the acute EI. Histopathology and decreased Muc5ac expression revealed an increased lung barrier breakdown and concomitant lung injury after THFx versus sham. EI prior trauma decreased lung injury. THFx increased not only the gene expression of pro-inflammatory markers but also the pulmonary infiltration with PMNL and apoptosis versus sham, while EI prior to THFx reduced those changes significantly. EI increased the THFx-reduced gene expression of Sost and reduced the THFx-induced expression of Wnt3a. While A20, RIPK4, and membranous β-catenin were significantly reduced after trauma, they were enhanced upon EI. Conclusion These findings suggest that acute EI alleviates the uncontrolled inflammatory response and lung barrier breakdown after trauma by suppressing the Wnt/β-catenin signaling pathway.